Penentu Jarak Tembak Berdasarkan Kerusakan Proyektil Timah Tanpa Jacket untuk Senjata Api Genggam Jenis Revolver S&W Kaliber .38 Spesial pada Target Tulang - Sudibyo Sudibyo (Universitas Airlangga, 2015)
Abstract This study aims to predict the shooting range based on damage the type of lead a projectile without jacket caliber.38 special fired from handguns kinds brand Revolver S & W caliber .38 specials. Based on the phenomenon of criminal cases of abuse handguns types Revolver and the fact that real data it was found that 8% of the amount of lead projectiles without jacket as forensic evidence, the condition has broken the deformed moderate to severe. The study was conducted at the Police Forensic Laboratory experimental method test-fired in the shooting box at short throw distance range of 0.5 to 6 meters , where the bone is positioned at the target position changes location every 0.5 meters, so the total number of shots is 12 times shot on 12 position target location, and finally obtained 12 variations of deformation projectile shot results. Stages test firing conducted through three stages as follows: 1). Phase sample preparation equipment and materials firearms, bullets and target bone. 2). Phase shooting target accurately. 3). Stages of deformation measurements and weighing projectile, arranged in the form of table data. Material samples of bullet used was the type of lead bullets without jacket caliber .38 special with technical specifications diameter of projectile 9.09 mm (real 9.05 mm), length of projectile 17.90 mm (real 18.61 mm), projectile material lead antimony, projectile weight of 10.25 grams, muzzle velocity (initial) 265 m / sec, rounded nose shape, coefficient of form C = 2, the ballistic coefficient i = 0,9 effective range or the distance accurately of 25 meters. Material samples of bone were used as target is 1694 SR veal ribs with bone hardness values (87 ± 1.5) shore, is used for the calibration test firing, a human skull age adults (≥ 35 years) with a value of hardness (78 ± 6 ) shore, is used as the target subjects of research, human ribs (costal C-3 / C-6) adult (≥ 35 years) with a value of hardness (69 ± 19.5) shore, is used as the target subjects of research. Keywords : deformation; projectiles; bones